A Biblical Evaluation of the Rite of Ziarah Kubur as Practiced by Javanese Muslims - Belcourt, Lew (Asian Journal of Pentecostal Studies, 2024)
The article explores the practice of ziarah kubur among Javanese Muslims, focusing on its divergence from classical Islam due to the influence of Folk Islam and pre-Islamic Javanese culture. Topics include the Javanese worldview, the practice of ziarah kubur among different classes of Javanese society, and the potential for contextualization of the rite for encountering the God of the Bible.